Long Take to Support Drama in the Film Women from Rote Island Director Jeremias Nyangoen - Asyraf, Muhammad; Fitri, Dynia (Kirana Publisher (KNPub), 2025)
This study aims to reveal, examine, and analyze how the long take technique can support the dramatic elements in the film Women From Rote Island directed by Jeremias Nyangoen. The research method used is qualitative with a descriptive analysis approach. The results of the study show that the application of the long take technique in the film Women From Rote Island proves that the long take does not stand alone, but is combined with other cinematographic elements such as camera movement, framing, camera angle, and lighting, which is in accordance with the theories of Bordwell, Thompson & Smith, Blain Brown, Joseph Mascelli. This combination successfully supports the dramatic elements of conflict, suspense, surprise, and curiosity. The effective use of long takes provides an opportunity for the audience to feel the tension and emotions of the characters directly.